Temporality and the torments of time - Hinton, Ladson (Journal of analytical psychology, 2015)
Immersion in time gives birth to consciousness, as well as conflict and torment. When human beings developed a sense of future, they also gained the ability to anticipate threats from nature or their fellow beings. They thereby created cultures that are bastions of survival, as well as places of poetry, art and religion where they could band together and reflect upon their common plight. The practice of psychoanalysis is in many ways a temporal process, a process of remembering, for owning and elaborating a past that gives us substance, thereby providing a basis for reflective consciousness. Stimulated by Freud's early writings, Lacan, Laplanche and their successors in particular have focussed extensively on time and psychoanalysis, and their views are a central point of this discussion. A substantial case study is offered that provides concrete examples of these perspectives. A multi-faceted view of temporality emerges, one that is more syncopated than linear or teleological. In conclusion, I will briefly discuss recent findings in the neuroscience of memory and ‘time travel’ that underpin contemporary psychoanalytic ideas in surprising ways. It is important to remember that acceptance of the contradictory nature of temporal experience can open space for increased freedom and playfulness.